Design and Optimization of Colorimetric Paper-Based Analytical Device for Rapid Detection of Allopurinol in Herbal Medicine - Rimadani Pratiwi; Rieda Nurwulan Septyani; Rossi Febriany; Febrina Amelia Saputri; Rina Fajri Nuwarda (International Journal of Analytical Chemistry)
Traditional herbal medicine in Indonesia is still in great demand and popular in society. The Indonesian government regulations state that herbal medicine should not contain chemical drug due to the toxic effect of uncontrolled consumption. Allopurinol is one of the drugs commonly added to herbal medicine for the treatment of chronic gout. Paper-based analytical device is one of the latest forms of analysis that has been widely used for the identification of chemical elements, environmental contamination, bacteria, and many more. In this study, experiments were conducted using Whatman filter paper No. 1, No. 2, and No. 4 and Whatman chromatography as a paper, and 9 colorimetric reagents were tested for allopurinol detection in herbal medicine. There were 5 specific reagents that reacted positively with allopurinol and only 3 reagents that can be applied to the paper, that is, Folin-Ciocalteu, Tollens, and p-DAB reagent. The results of the optimization show that the most optimal immersion time was 60 minutes with a drying time of 30 minutes at 50°C. Each filter paper has different characteristic; however, there was no significant difference when all of the papers were used as PAD for allopurinol detection.